Consensus-building during the Becoming Breastfeeding Friendly (BBF) initiative in Samoa: A qualitative content analysis - Katherine Daiy; Kendall Arslanian; Courtney Choy; Analosa Manuele-Magele; Christina Soti-Ulberg; Amber Hromi-Fiedler; Nicola Hawley; Rafael Pérez-Escamilla (Public Library of Science (PLoS), 2023)
The Becoming Breastfeeding Friendly (BBF) initiative provides countries with an evidence-based toolbox to improve the national breastfeeding environment by assessing and developing a plan to effectively scale up well-coordinated national policies and programs. BBF is carried out by a multi-institutional, intersectoral committee of experts, convening across five committee meetings designed to produce policy recommendations that can be implemented in the country's context. Samoa successfully completed the BBF initiative in 2018, resulting in the institution of breastfeeding policy in hospitals and the establishment of lactation rooms within government ministries. An important step in informing the success of future breastfeeding scale-up initiatives is understanding how consensus is built. This study aimed to investigate how the BBF Samoa committee built consensus. We conducted a content analysis of audio recordings of three BBF Samoa meetings (meetings 1, 2 and 4), meeting minutes, and meeting notes using an a priori operational consensus-building framework. We used a combination of deductive and inductive approaches to: a) evaluate the data against existing, a priori criteria for consensus-building and b) identify emergent ways in which the BBF Samoa committee may have achieved consensus. We identified 6 themes, 2 meta-subthemes, and 16 subthemes. The 6 themes, largely defined by the a priori framework, represented key components of successful consensus-building. The 2 meta-subthemes described two overarching methods of consensus-building: "process-led" (i.e., inherent to the BBF process itself) and "organic" (unique/specific to the committee). Lastly, the 16 subthemes described more specific ways that the committee reached consensus. The detailed manualization of the BBF process, its reliance on data, and its transparent and engaged committee process were key for reaching consensus on BBF scores and recommendations in Samoa. Our study contributes to the understanding of how effective breastfeeding policy recommendations are made, using a methodology that can be applied beyond the topic of breastfeeding.